Blastocystis spp. Infection in immunocompetent and immunocompromised individuals - Milagros del Valle Figueroa Lara; Lourdes del Valle Hernández-Gil; Génesis Esperanza Pérez-Gutiérrez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
Blastocystis spp. it is a controversial parasite that has undergone multiple reclassifications and whose pathogenic role for man remains uncertain. To relate the presence of Blastocystis spp. in immunocompetent and immunocompromised patients, in the absence or presence of symptoms, morphometry and number of parasites in individuals were evaluated, from the of the University Hospital "Antonio Patricio de Alcalá", Cumaná, Sucre state, with prior informed consent, during the months September to December 2018. Each fecal specimen was analyzed by direct examination, the semi-quantification of the chromist was done in ten consecutive fields of 40X, the morphometric analysis by means of fecal smears stained with Giemsa observed at 100X and micrometry. Of the total number of patients evaluated (n = 162), the chromist ranked first in prevalence in immunocompetent (32.86%), of the immunocompromised group the most affected were malnourished patients (8.02%), followed by oncological and with HIV/AIDS infection with 5.56% and 1.85% respectively. In both groups, symptomatic patients were presented, the most common clinical manifestations being abdominal pain, diarrhea and flatulence; with respect to quantification, it was possible to show that a small group of cancer patients with malnutrition who presented symptoms had counts of less than 5 parasites per field. When performing the morphometric analysis, the central body shape was the only one identified in both groups, coinciding with the results obtained in the direct examination, the evaluated morphotypes presented diameters >10 μm, being larger in immunocompromised patients than in immunocompetent patients (p <0.05).